2002
DOI: 10.1016/s1388-2457(02)00003-2
|View full text |Cite
|
Sign up to set email alerts
|

Semantic bias, homograph comprehension, and event-related potentials in schizophrenia

Abstract: Objectives-It is controversial whether a semantic processing bias for strong associates is present in schizophrenia, and unknown whether the language abnormalities observed in schizophrenia can be attributed to dysfunctions early or late in cognitive processing. Combined behavioral and eventrelated potential (ERP) data can indicate the nature and timing of such abnormalities.Methods-Sensibility judgements of dominant and subordinate homograph sentences were measured in 12 schizophrenia patients and 13 normal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 46 publications
(61 reference statements)
9
48
1
Order By: Relevance
“…In a recent study (Salisbury et al, 2007; see also Salisbury et al, 2002), schizophrenia patients at initial hospitalization, bipolar disorder patients, and healthy controls did not differ from each other in the amplitude of frequency-change MMN. At a follow-up evaluation 18 months later, only the patients with schizophrenia showed smaller MMN amplitude; this was highly correlated with a reduction in left-hemisphere Heschl Gyrus volume.…”
Section: Schizophreniamentioning
confidence: 86%
See 1 more Smart Citation
“…In a recent study (Salisbury et al, 2007; see also Salisbury et al, 2002), schizophrenia patients at initial hospitalization, bipolar disorder patients, and healthy controls did not differ from each other in the amplitude of frequency-change MMN. At a follow-up evaluation 18 months later, only the patients with schizophrenia showed smaller MMN amplitude; this was highly correlated with a reduction in left-hemisphere Heschl Gyrus volume.…”
Section: Schizophreniamentioning
confidence: 86%
“…Other studies, however, have presented a more coherent picture of preserved semantic access to individual word meanings, combined with difficulty building or maintaining a semantic representation based on longer sequences of words. Salisbury et al (2002) found that schizophrenic patients fail to use context to disambiguate homographic words, but instead persist with the more frequent word meaning. Depending on the experimental stimuli, this deficit can lead to an N400 effect that is larger or smaller than in controls.…”
Section: Neurocognitive Analyses Of Complex Symptomsmentioning
confidence: 96%
“…Four types of nouns were presented, 25 of each type: Unambiguous (e.g., The door was shut, The butter was melting, The lion was roaring); Dominant homograph (e.g., The panel was oak, The plane was flying, The horn was blaring); Subordinate homograph (e.g., The panel was voting, The plane was sharp, The horn was pointy); and Nonsensical (incongruent endings for unambiguous nouns, e.g., The radio was fluffy, The salad was printed, The hammer was cloudy). For description of the stimuli used and normative data bases, see Salisbury et al (2002). WAIS-III (Wechsler, 1997) Information and Vocabulary scores were used for measures of semantic memory, and WAIS-III symbol-digit coding and the Trails B test were used as measures of working memory.…”
Section: Methodsmentioning
confidence: 99%
“…In a separate line of research, we have examined comprehension of and N400 to subordinate homographs to explicate thought disorder in psychosis (e.g., Salisbury, Shenton, Nestor, & McCarley, 2002). Homographs are words that are spelled the same but have different meanings (e.g., an oak panel, a voting panel).…”
Section: Introductionmentioning
confidence: 99%
“…As far as language disturbances in SZ are concerned, it is known that patients with this disease generally have difficulty processing semantic aspects of language (Anand, Wales, Jackson, & Copolov, 1994;Blaney, 1974;Nestor et al, 2001;Paulsen et al, 1996), combining semantic and syntactic information (Condray, Steinhauer, Cohen, van Kammen, & Kasparek, 1999;Condray, Steinhauer, van Kammen, & Kasparek, 2002;Sitnikova, Salisbury, Kuperberg, & Holcomb, 2002;Thomas, King, Fraser, & Kendell, 1990), creating lexico-semantic associations (Salisbury, O'Donnell, McCarley, Nestor, & Shenton, 2000;Salisbury, Shenton, Nestor, & McCarley, 2002;Sitnikova et al, 2002;Titone, Levy, & Holzman, 2000), and accessing and using lexical knowledge (McKenna & Oh, 2005). They also exhibit deficits in verbal fluency, especially in category fluency (Bokat & Goldberg, 2003;Kremen, Seidman, Faraone, & Tsuang, 2003).…”
Section: Introductionmentioning
confidence: 99%